KENALI DAN CEGAH DEMAM BERDARAH DENGUE SEBAGAI UPAYA PENCEGAHAN DAN PENANGGULANGAN PENYAKIT - Arisandi, Desto; Bulu, Martinus Tagu; De Jesus, Maria Carolina; Saraswati, Farikhatun Nisaa; Mosa, Rambu Pedi; Nono, Arianto; Bolosan, Fabio Andre; Dapa Ole, Ericson Umbu Robaka; Nadifah, Fitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) is transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. Efforts that can be made to reduce the incidence of dengue fever are through the 3M plus movements (draining, burying and covering) and carrying out preventive activities such as sprinkling larvicide powder, using mosquito repellent, and planting mosquito repellent plants. The aim of this community service is to increase public knowledge about recognizing and preventing dengue fever as an effort to prevent and control the disease. The activities were carried out at Padukuhan Nologaten, Caturtunggal Village, Sleman Regency, Yogyakarta Province in May-June 2024. The activities carried out include situation analysis, preparation, implementation, monitoring and evaluation, and analysis and reporting. The participants of this activity numbered 37 people with the majority aged 46-65 years (48%) and college education background (48%). The average level of community knowledge about the prevention and control of dengue fever before counseling (pre-test) was good (89%) and sufficient (11%) and after counseling, the level of community knowledge increased to good (95%).